Added Benefits: The Link Between Work-Life Benefits and Organizational Citizenship Behavior - Lambert, Susan J. (Academy of Management Journal, 2000)
Countering arguments that employee benefits are unrelated to both worker performance and perceived organizational support, I developed and estimated a model that links work-life benefits to organizational citizenship behavior directly, through obligations incurred as a result of social exchange, and indirectly, through enhanced perceptions of organizational support. Significant, positive relationships were found between workers' assessments of the usefulness of work-life benefits and three measures of organizational citizenship. Although perceived benefit usefulness contributed to perceived organizational support, perceived organizational support did not in turn foster organizational citizenship as measured in this study.